Individual Differences in Religious Motivation Influence How People Think - Michaels, Jay L. ca. 20./21. Jh. (Journal for the scientific study of religion, 2021)
Motives matter and may have implications for how people cognitively experience meaning through religion and spirituality. Specifically, intrinsically motivated people perceive religion and spirituality are more central to meaning in life, which should promote a tendency to adopt more coherent, expansive cognitive representations. In contrast, extrinsically motivated people may adopt narrower cognitive representations since their motivation is more proximally oriented. The present study tests these possibilities by examining how religious motivation relates to action identification (tendency to use coherent, higher-level cognitive representations). Results from 630 participants revealed that among religious people, intrinsic and extrinsic-personal religious motivations indirectly influence higher-level action identification through strength of spiritual beliefs. These relationships were not evident among nonreligious people. Furthermore, extrinsic-social religious motivation and religious service attendance did not relate to action identification. These findings demonstrate that religious motivation differences are consequential for the action identities people rely upon to form a sense of meaning.